2019
DOI: 10.1108/jeee-06-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Micro-credit as catalyst for improving rural livelihoods through agribusiness sector in Indonesia

Abstract: Purpose This paper aims to analyse a simultaneous role of micro-credit in intensive farming to improve rural prosperity and to determine factors affecting farmers to access micro-credit and to adopt technologies. Design/methodology/approach This paper uses a concept of technological change as the underlying theory. The analysis is conducted using structural equation modelling based on data compiled from a survey that interviewed 220 of farm-households. Samples of the study were randomly selected from chili f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…In financing such funds, selecting the credit structure (Bai, at. All., 2019) of financial assets is dominant as a fact that determines a potential agro-producer (Mariyono, 2019), which is also the subject of research in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In financing such funds, selecting the credit structure (Bai, at. All., 2019) of financial assets is dominant as a fact that determines a potential agro-producer (Mariyono, 2019), which is also the subject of research in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, these countries are behind high-income countries in terms of agricultural productivity. According to Mariyono (2019), the widespread use of technology in agriculture and increased productivity are important for economic growth and rural development in emerging economies. However, it is observed that the effects of agricultural productivity are mostly neglected in recent studies on economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Tomato (Solanum lycopersicum L.) is a vegetable with great potential for development in East Java because of its high economic value [1,2] and can contribute to the household economy when it is intensively cultivated using appropriate technology [3,4]. In 2017 and 2018, tomato production in East Java was 15.6 t•ha −1 and 16.5 t•ha −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%